The Effect of Work Environment, Career Development, and Incentives on Employee Job Satisfaction at PT XYZ - Yulia Dwi Lestari; Mohamad Lutfi; Mochamad Rizal (International Journal of Management Science and Information Technology, 2026)
This study seeks to understand the impact of work, and thus analyze how goal setting can lead to work-life outcomes, as a productive transformation. This is significant because post-COVID adjustments in work modes and rhythms, along with shifts in international competitive conditions, are bringing greater economic pressures to the workplace. For businesses, this means that employee satisfaction with their jobs must remain high if strong worker productivity is to be maintained. This, in turn, leads to increased employee and department loyalty, which can expand their recruitment capabilities. This study adopted a quantitative research paradigm and followed an exploratory survey framework. Primary data were collected by administering a Likert-scale questionnaire to 120 randomly selected employees from various parts of PT XYZ. Data analysis was conducted using a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The researchers found that the magnitude of rewards had a positive influence on job satisfaction of PT XYZ employees. Rewards, particularly those given in the form of performance-based bonuses and additional regular salary, directly resulted in excellent job satisfaction ratings. At the same time, in partial testing, the work environment and career development both failed to show a significant impact on job satisfaction. This research is limited because the data comes from only one company and is based on staff questionnaires. These findings are important for PT XYZ, which must replace its current three-tier incentive system with a simpler and more transparent performance-based system to improve job satisfaction and reduce staff turnover, or remain as is and see its competitiveness in the future.